1977
DOI: 10.1073/pnas.74.6.2556
|View full text |Cite
|
Sign up to set email alerts
|

Ligands and oxidants in ferrihemochrome formation and oxidative hemolysis

Abstract: We have investigated the effect of size of a single neutral ring substituent on the induction of hemolytic anemia and the formation of a ferrihemochrome by substituted phenylhydrazines. The severity of induced anemia decreased with increase in size of a halogen atom or an alkyl group ortho to the hydrazino group, little anemia resulting from 2-iodophenylhydrazine and no anemia from 2-tert-butylphenylhydrazine. The size of a halogen atom or an alkyl group at the meta or para position had relatively little effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
2

Year Published

1978
1978
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 56 publications
1
22
2
Order By: Relevance
“…Fe"H202 + C6H5NHNH2--Fe"I + 2H20 + C6H5N:NH or FeNVO + C6H5NHNH2 -> Fe"i + H20 + C6H5N:NH. [4] Formation of a second molecule of phenyldiazene agrees with the finding (23) that two molecules of 02 per oxyheme were rapidly consumed in the reaction of an excess of phenylhydrazine with oxyhemoglobin.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Fe"H202 + C6H5NHNH2--Fe"I + 2H20 + C6H5N:NH or FeNVO + C6H5NHNH2 -> Fe"i + H20 + C6H5N:NH. [4] Formation of a second molecule of phenyldiazene agrees with the finding (23) that two molecules of 02 per oxyheme were rapidly consumed in the reaction of an excess of phenylhydrazine with oxyhemoglobin.…”
Section: Discussionsupporting
confidence: 78%
“…Studies from this laboratory indicated that substituents on the benzene ring affected the hemolytic activity of substituted phenylhydrazine and the binding ofsubstituted phenyldiazenes to methemoglobin in parallel fashion (4). Subsequent studies showed, however, that the hemolytic activity of ring-substituted nitrosobenzenes was not related to their affinities as ligands of deoxyhemoglobin (5).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…may be due to the action of free radicals and other activated oxygens [12][13][14][15][16][17]. Life itself, however, is protected against these oxidant stresses by reducing enzymes such as superoxide dismutase, catalase, GSH-Px, etc., and other free radical scavengers, like vitamins A, B2, C, E (tocopherol), and ubiquinone (CoQ).…”
Section: Discussionmentioning
confidence: 99%
“…Breakdown of the diazine (PhN = NH) is fast and 02--dependent, but it is stabilized in the presence of methemoglobin by formation of hemichrome (43)(44)(45)(46). With APH the diazine also forms hemichrome, but does not readily break down to benzene (44).…”
Section: Nh-nhcoch IIImentioning
confidence: 99%